Software-Defined SDR Radio System - Korotkova Larisa Alexandrovna; Khudoiberganov Shavkat Karimovich (Scientific Trends, 2024)
The article presents software, which is one of the types of computer system support, along with technical (hardware), mathematical, informational, linguistic, organizational, methodological and legal support.
Keywords: Software, Software-defined radio, digital-to-analog converters, feeding automatic gain control.